Algerian Economic Diplomacy and the Imperatives of Regional Integration in Africa: A Study of Border Cooperation Policy (2019–2029) - Belmahdi, Hadjer; Khelfa, Salaheddine (Journal of Ecohumanism, 2026)
The African orientation of Algerian foreign policy has witnessed a notable shift since 2019, with Algeria prioritizing the activation of economic diplomacy as a key tool for achieving shared development and regional integration. This study aims to analyze the reality of cross-border cooperation between Algeria and its African neighbors as one avenue of economic diplomacy, focusing on existing and anticipated regional integration mechanisms by 2029. The study also seeks to highlight the qualitative shift in Algeria’s African approach, where Africa is no longer merely a geographical extension but a strategic space for shared development. In this vision, Algeria combines economic and diplomatic dimensions, making cross-border integration a cornerstone for achieving regional security and shared continental progress.The research paper employs a comparative analytical methodology, combining descriptive approaches with field studies of cross-border projects (such as the Trans-Saharan Highway and logistics zones), to assess their alignment with Algeria’s new vision for fostering effective and sustainable African partnerships. The study concludes that the success of this vision depends on activating the shared infrastructure and intensifying field economic diplomacy, so that borders become bridges for integration, not lines of separation, in order to achieve the principle of "development through security and cooperation".